2021
DOI: 10.2147/pgpm.s292556
|View full text |Cite
|
Sign up to set email alerts
|

Influence of UGT1A1 *6/*28 Polymorphisms on Irinotecan-Related Toxicity and Survival in Pediatric Patients with Relapsed/Refractory Solid Tumors Treated with the VIT Regimen

Abstract: The association between UGT1A1*6/*28 polymorphisms and treatment outcomes of irinotecan in children remains unknown. This retrospective study investigated the influence of UGT1A1*6/*28 polymorphisms on irinotecan toxicity and survival of pediatric patients with relapsed/refractory solid tumors. Methods: The present study enrolled a total of 44 patients aged younger than 18 years at Sun Yat-sen University Cancer Center between 2014 and 2017. Results: There were 26 boys and 18 girls; the median age at first VIT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
(100 reference statements)
0
5
0
Order By: Relevance
“… 23 Meanwhile, the VIT (oncovin, irinotecan, and temozolomide) regimen in 44 pediatric patients with relapsed/refractory solid tumors was associated with increased irinotecan‐related toxicity but tended to reduce the patient overall survival. 24 In our study, patients with UGT1A1 polymorphisms had an increased frequency of grade 4 leukopenia after IREC therapy but had no increase in FN or BSI compared with wild‐type patients. Meanwhile, four of the six patients with OR had a UGT1A1 polymorphism.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“… 23 Meanwhile, the VIT (oncovin, irinotecan, and temozolomide) regimen in 44 pediatric patients with relapsed/refractory solid tumors was associated with increased irinotecan‐related toxicity but tended to reduce the patient overall survival. 24 In our study, patients with UGT1A1 polymorphisms had an increased frequency of grade 4 leukopenia after IREC therapy but had no increase in FN or BSI compared with wild‐type patients. Meanwhile, four of the six patients with OR had a UGT1A1 polymorphism.…”
Section: Discussionmentioning
confidence: 46%
“…In contrast, an irinotecan‐containing chemotherapy regimen (carboplatin, dexamethasone, etoposide, and irinotecan [CDE‐11]) for adult diffuse large B‐cell lymphoma has been shown to improve prognosis in patients with the UGT1A1 *6 polymorphism 23 . Meanwhile, the VIT (oncovin, irinotecan, and temozolomide) regimen in 44 pediatric patients with relapsed/refractory solid tumors was associated with increased irinotecan‐related toxicity but tended to reduce the patient overall survival 24 . In our study, patients with UGT1A1 polymorphisms had an increased frequency of grade 4 leukopenia after IREC therapy but had no increase in FN or BSI compared with wild‐type patients.…”
Section: Discussionmentioning
confidence: 99%
“…Ethnic differences in UGT1A1 gene polymorphism are closely associated with AEs of irinotecan, 21 23 but its efficacy remains uncertain. 15 , 24 , 25 Most studies believed that patients with homozygous UGT1A1*28 mutation would have serious toxic reactions, and it was suggested to reduce the dosage of irinotecan. 23 , 24 , 26 , 27 To reduce the toxicity of irinotecan, FDA proposed that patients should be genotyped for UGT1A1*28 polymorphism before treatment with irinotecan.…”
Section: Discussionmentioning
confidence: 99%
“… 11 , 12 Multiple meta-analyses showed that the polymorphisms of UGT1A1 * 6 and UGT1A1 * 28 genes were significantly associated with irinotecan-induced severe diarrhea and neutropenia, but this conclusion is still controversial due to the different frequencies of UGT1A1 genotypes in eastern and western countries. 13 16 …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, UGT1A1 is an enzyme that conjugates the active metabolite of irinotecan to glucuronic acid to facilitate elimination [24]. Several variants have been recognized, with the UGT1A1∗6 and UGT1A1∗28 forms potentially contributing to worse chemotherapy associated side effects [31,32]. Studies have attempted to assess the value of genotyping for patients receiving irinotecan, with a benefit in cost and toxicity noted in several [33,34 ▪ ].…”
Section: Pharmacogenetics and Treatment Regimensmentioning
confidence: 99%